2019
DOI: 10.1111/jar.12655
|View full text |Cite
|
Sign up to set email alerts
|

Using a dual‐task paradigm to investigate motor and cognitive performance in children with intellectual disability

Abstract: Background The purpose of the current study was to evaluate the effects of dual‐task (DT) constraints on walking performance in children with intellectual disability (ID). Methods Fifteen children with intellectual disability and fifteen age‐matched typically developed children were asked to walk at a preferred speed: along a path (baseline condition), while carrying a glass of water and while quoting animal names. Results The present study findings showed that DTs affect walking performance of both typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 54 publications
(77 reference statements)
1
17
0
Order By: Relevance
“…When people perform a dual task, there is usually a deterioration in one or both tasks’ performance [ 24 ]. For example, some studies showed that walking while simultaneously carrying a cup [ 25 ] or transferring coins from one pocket to the other [ 26 ] reduces the gait performance compared to only walking. Others studies reported that maintaining an upright position while performing a cognitive task decreases the postural stability compared to performing a single task [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…When people perform a dual task, there is usually a deterioration in one or both tasks’ performance [ 24 ]. For example, some studies showed that walking while simultaneously carrying a cup [ 25 ] or transferring coins from one pocket to the other [ 26 ] reduces the gait performance compared to only walking. Others studies reported that maintaining an upright position while performing a cognitive task decreases the postural stability compared to performing a single task [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, evidence suggests that II‐athletes have heightened susceptibility to DT effects, which may be attributed to their smaller cognitive resource pool due to impairment. Several studies observed greater performance decline in DT situations in II‐children 14,15 as well as II‐adults 16,17 compared to their non‐II‐counterparts. In contrast, greater resistance to DT effects has been demonstrated for elite athletes from various sports like athletics, 3 gymnastics, 18 and table tennis 19 .…”
Section: Introductionmentioning
confidence: 99%
“…This is because the central nervous system, which regulates motor and cognitive abilities, often shows some degree of delay in individuals with IDD (Reguera-García et al, 2021). In addition, individuals with IDD may have several functional disorders of balance (Bahiraei et al, 2018;Bahiraei, 2019), motor (Cleaver et al, 2009;Galli, Rigoldi, Mainardi, et al, 2008;Giagazoglou et al, 2013), and cognitive ability (Galli, Rigoldi, Mainardi, et al, 2008;Kachouri et al, 2020). Delays in motor and cognitive development affect the gait patterns of individuals with IDD because their efficiency and performance depend on the coordination between these systems (Lopes Pedralli & Schelle, 2013).…”
Section: Introductionmentioning
confidence: 99%